How Does Terrorism Affect Individuals' Wellbeing? - Alex Bryson; George MacKerron (Institute of Labor Economics (IZA), 2018)
This paper is the first to exploit high-frequency data to measure the impact of terrorist-related incidents (TRIs) on individuals' momentary happiness and anxiety. We show the impact of TRIs varies with the nature of the incident, the individual's physical proximity to it, and the time that has elapsed since the incident. TRIs have a substantial effect on individuals' momentary happiness and anxiety levels, but the effect is short-lived and is largely confined to incidents that lead to the death of victims and incidents within a twenty kilometre radius.
Keywords: I31; 330; happiness; anxiety; wellbeing; conflict; bombings; killings; shootings; terrorism; Northern Ireland